Breastfeeding and weaning practices of the ancestral Ohlone Indians of California: A case study using stable isotope analysis of bone collagen. (19th June 2018) - Gardner, Karen S.; Bartelink, Eric J.; Martinez, Antoinette; Leventhal, Alan; Cambra, Rosemary
Abstract: Variation in human breastfeeding and weaning practices is subject to changing social pressures and norms, as well as individual agency. This paper presents a case study from the Yukisma Mound (CA‐SCL‐38), a prehistoric site in the San Francisco Bay Area, which was used as a ceremonial and cemetery space by the ancestral Ohlone Indians between 780 and 230 cal yearsbp . Stable carbon and nitrogen isotope values from bone collagen of 201 individuals, including 26 subadults, are analysed. The Weaning Age Reconstruction with Nitrogen isotope analysis package in R is used to model expected δ 15 N values of infant bone collagen, against which measured δ 15 N values reveal individual variation in weaning practices. Infants from this burial sample were exclusively breastfed until approximately 0.8 years (maximum density estimation (MDE), marginal probability = 0.0456), and completely weaned by around 4.4 years (MDE, marginal probability = .0409). Range of variation in adult diets is used as a baseline of comparison, in addition to mean δ 15 N values of adult females, to better consider supplementary food options, and to avoid the assumption of a homogeneous maternal diet. Comparison with weaning data from contemporaneous regional sites, drawn from studies using tooth dentin of individuals who survived childhood, reveals that introduction of complementary foods and cessation of breastfeeding occurred somewhat later at the Yukisma Mound. This contrast suggests prolonged supplementation with breastmilk for children who expressed nutritional stress or disease. Variation in weaning trajectories is further interpreted using δ 13 C values to identify individuals with elevated δ 15 N values due to supplementation with high trophic level foods (e.g., freshwater fish and marine foods). Changes in weaning practices are demonstrated by comparison of this sample to ethnohistoric accounts of the Ohlone. This study provides an example of collaborative research with descendent populations and of making the most of available materials.